Differences in Non-volatile Chemical Components between Liupao Tea and Its Raw Material - Ying YANG; Wanjun MA; Qiushuang YOU; Gaozhong YANG; Zhi LIN; Haipeng LÜ (Shipin gongye ke-ji)
The differences in the major non-volatile chemical components between Liupao tea (LPT) and its raw material (LPM) were analyzed using ultra performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) alongside other analytical methods, and the key differential metabolites were identified through multivariate statistical analyses. Results indicated that the levels of water extracts, tea polyphenols, water-soluble carbohydrates, free amino acids, and total flavonoids in LPT were significantly decreased compared with those observed in LPM (P<0.05). A total of 569 chemical compounds were identified in both LPT and LPM, which could be classified into 11 groups, primarily including lipids, amino acid and their derivatives, flavonoids, alkaloids, and others. Furthermore, 146 differential metabolic compounds were detected (VIP>1, P<0.01), among which 32 exhibited significant increases while 114 showed significant reduced in LPT compared to LPM. Additionally, further analysis revealed that the relative concentrations of key flavor components such as catechins and amino acids, as well as color-related components, such as theaflavins and flavonoid glycosides, were significantly lower in LPT compared with LPM (P<0.01). These findings elucidate the differences in major non-volatile chemical components between LPM and LPT, and may provide a foundation for understanding the chemical basis of the quality formation of Liupao tea.